Nekaj misli o dramaturški vlogi značaja v Sofoklovih tragedijah - Senegačnik, Brane (Keria (Ljubljana), 2000)
In the comparison with the antique and traditional notion of character (personality) the modern notion proves far more appliable for the analysis of antique (ancient) drama. Stil more, this modern, extended notion of character (personality) opens the door to a new interpretation of Sophocles' (as well as Aeschylus' and Euripides') dramaturgy. One does not do justice to his dramas judging their heros by Shakespearian or romantic standards; Sophocles, due to demands of his dramaturgy technique, very often gives only a hint of what is a true nature of his heros, yet this hint can enable modern reader to form himself a picture of personalities on the stage.
Keywords: dramatika; grška književnost; literarne študije; Sophocles; tragedija; značaj